Benefits of Participation in Student Organization in Tourism Education: Professional and Working Opportunities Through Experience - Ningrum, Lestari; Azalia, Monica (Jurnal Penelitian Pariwisata, 2018)
Extracurricular organizations are beneficial to college students. They help in bringing students and institutions together, let students interact in a non-formal atmosphere, and allow students to strengthen their leadership and communication skills. There are at least what books, articles, and advisors will tell the students. In today’s society, employers are hiring students more on what they can do, not their grade point average. Participating in extracurricular organizations shows future employers that students can handle school, work, and other activities, which in turn shows responsibility and organization. Do students really understand this?. Sometimes labeled as "the other education", participation in extracurricular activities provides opportunities for students to apply classroom knowledge to real world settings and develops skill that will assist in the practical realities of living after graduation. This research uses qualitative phenomenological, which aims to describe the activities of students during the process of becoming members of student organizations on campus, and to share her experiences and the benefits of the activities of the organization that she attended over the years. Using a sample of one student. The results of this study show that by holding several important positions in student organizations on campus and playing an active role, it is very useful, because their performance professional and ending with gaining experience teaching children of primary school, and became a student independent, self-confident and has experience in the organization before she underwent training in the industry and work upon graduating from college in 2018.